The Impact of ACEs on BMI: An Investigation of the Genotype-Environment Effects of BMI - Schlauch, Karen A.; Read, Robert W.; Neveux, Iva; Lipp, Bruce; Slonim, Anthony; Grzymski, Joseph J. (Frontiers in Genetics, 2022)
Adverse Childhood Experiences are stressful and traumatic events occurring before the age of eighteen known to cause mental and physical health problems, including increased risk of obesity. Obesity remains an ongoing national challenge with no predicted solution. We examine a subset of the Healthy Nevada Project, focusing on a multi-ethnic cohort of 15,886 sequenced participants with recalled adverse childhood events, to study how ACEs and their genotype-environment interactions affect BMI. Specifically, the Healthy Nevada Project participants sequenced by the Helix Exome+ platform were cross-referenced to their electronic medical records and social health determinants questionnaire to identify: (1) the effect of ACEs on BMI in the absence of genetics; (2) the effect of genotype-environment interactions on BMI; (3) how these gene-environment interactions differ from standard genetic associations of BMI. The study found very strong significant associations between the number of adverse childhood experiences and adult obesity. Additionally, we identified fifty-five common and rare variants that exhibited gene-interaction effects including three variants in the CAMK1D gene and four variants in LHPP; both genes are linked to schizophrenia. Surprisingly, none of the variants identified with interactive effects were in canonical obesity-related genes. Here we show the delicate balance between genes and environment, and how the two strongly influence each other.